2020
DOI: 10.3390/geriatrics5040074
|View full text |Cite
|
Sign up to set email alerts
|

Is Promotion of Mobility in Older Patients Hospitalized for Medical Illness a Physician’s Job?—An Interview Study with Physicians in Denmark

Abstract: : The aim of this study was to identify the most common barriers and facilitators physicians perceive regarding their role in the promotion of mobility in older adults hospitalized for medical illness as part of on an intervention to promote mobility. Twelve physicians at two medical departments were interviewed face-to-face using semi-structed interviews based on the Theoretical Domains Framework. The physicians’ perceived barriers to promoting mobility were: the patients being too ill, the department’s inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(46 citation statements)
references
References 64 publications
1
45
0
Order By: Relevance
“…Although the patients in our study did receive three meals per day, this was not re ected in their peak times and may indicate that meals were consumed close to or in bed. This is well in line with recent studies by our research group, Pedersen et al 2020 [52] and Stefánsdóttir et al [53], that investigated facilitators and barriers for mobility during hospitalization. They found that the barriers for mobility in this patient group were the provision of excessive service and care by the department, a culture of bed rest, and lack of encouragement by health care professionals to motivate the patients to increase activity.…”
Section: Baseline Characteristicssupporting
confidence: 91%
“…Although the patients in our study did receive three meals per day, this was not re ected in their peak times and may indicate that meals were consumed close to or in bed. This is well in line with recent studies by our research group, Pedersen et al 2020 [52] and Stefánsdóttir et al [53], that investigated facilitators and barriers for mobility during hospitalization. They found that the barriers for mobility in this patient group were the provision of excessive service and care by the department, a culture of bed rest, and lack of encouragement by health care professionals to motivate the patients to increase activity.…”
Section: Baseline Characteristicssupporting
confidence: 91%
“…The results showed multiple reasons for the physicians’ lack of commitment. Firstly, the physicians found the interior of the departments unfit for the intervention [ 63 ]. Secondly, the physicians did not see mobility as part of their job and responsibility.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, the physicians did not see mobility as part of their job and responsibility. Finally, the physicians expressed lack of time and resources and therefore unwillingness to accept additional workload [ 63 ]. The consequence of the physicians’ lack of commitment in the implementation of the intervention was that the implementation champions and managers made multiple modifications to the intervention to enable the physicians’ to participate.…”
Section: Resultsmentioning
confidence: 99%
“…Also, Pedersen et al 2020 conducted a qualitative study that investigated facilitators and barriers for mobility during hospitalization, by semi-structed interviews with twelve physicians at two medical departments and Stefánsdóttir et al explored 20 old (+65) medical patients’ experiences with mobility during hospitalization more generally, and with an intervention to increase in-hospital mobility. Pedersen et al 2020 [ 59 ] and Stefánsdóttir et al [ 60 ] found that barriers for mobility in older medical patients were the provision of excessive service and care by the department, a culture of bed rest, and lack of encouragement by health care professionals to motivate the patients to increase activity. Also, Stefansdottir et al reported that the staff brought food, beverages, and clothes to patients, including those who were able to get out of bed and walk.…”
Section: Discussionmentioning
confidence: 99%